Hong Kong’s media representations of China amid COVID-19: a corpus-assisted critical discourse analysis - Hu, Xiaolin; Kasimon, Diyana Nawar; Wan Abas, Wan Anita (Redfame Publishing Inc., 2024)
Since the COVID-19 outbreak, many scholars have noted the significant value of studying media representations of the COVID-19 pandemic everywhere. However, when observing these research results, one will find that more research results are about the Western media, and there are few reports about the Chinese media on the COVID-19 pandemic. This study employs corpus-assisted critical discourse analysis to examine what kinds of discourse Hong Kong media use to represent China in the news. The Sing Tao Daily was chosen for the study because it has been in existence for a long time and has readers all over the world. Its coverage of China COVID-19 will affect Hong Kong people's perception of their motherland. Hong Kong is unique in that it has just recently returned to China. The Hong Kong media's coverage of mainland China will affect China's national image in the minds of Hong Kong people. This study aims to examine what discourses are used by the Hong Kong news media in their coverage of China's fight against the epidemic and what kind of national image of China is presented to the Hong Kong and global audiences. The analysis reveals that China is presented as a victim, and an advantageous cooperative country. China is a responsible big country that has assumed the responsibility of helping countries in difficulty and is a united country. China's actions have had a positive impact on global humanitarian ideology. This study illustrates how the media can effectively utilize discursive strategies to promote cooperation and build a country's image in the midst of a global health crisis.